Penentuan Harga Pokok Produksi Dan Pelaporan Keuangan Untuk Usaha Rintisan Menggunakan Google Spreadsheet - Paru, Sara Marlyn; Bleskadit, Novalia Herlina; Pangayow, Bill J.C (The Community Engagement Journal, 2024)
Small, Micro, and Medium Enterprises (SMEs) in Indonesia account for 60% of GDP and employ 116 million individuals. The extensive market share in Indonesia and the significant customer interest in MSME products present potential for diverse entities to develop highly competitive innovative items. The FIM community in Jayapura is an organization comprised of young Papuans dedicated to a social mission in education. In 2023, community members established a commercial venture by producing tote bags featuring Papua motifs and patterns, thereafter offered to friends and family. The sales results were positively accepted by consumers and created new prospects for the FIM community to manufacture other items. Recognizing the deficiencies among community members, including inadequate knowledge of production costs, profit and loss assessments, financial reporting, and the absence of market share awareness, this service initiative aims to improve the comprehension of FIM community members concerning the determination of production costs, recording of financial transactions, calculations of profit and loss, financial reporting, and market share analysis through the application of SWOT analysis and Business Model Canvas. This community service project aims to enable participants to independently compute production costs, document transactions and financial reports, assess business profits and losses, and evaluate market share.